Ultrasound‐Guided Cervical Nerve Root Block for the Treatment of Acute Cervical Herpes Zoster: A Randomized Controlled Clinical Study. Issue 5 (29th March 2019) - Zheng, Shuyue; Li, Xiuhua; Yang, Xiaohui; He, Liangliang; Xue, Yanyan; Yang, Zhanmin
Abstract: Objectives: To evaluate the efficacy and safety of ultrasound‐guided cervical nerve root block (CRB) on acute pain and its preventive effects on post‐herpetic neuralgia (PHN) in patients with cervical herpes zoster (HZ). Methods: 140 recruited participants were randomized 1:1 to receive ultrasound‐guided CRB with either mixed drug liquid (treatment group) or similar looking placebo (placebo group). All patients received a 7‐day course of oral antiviral treatment, pregabalin, and analgesics as needed. The primary efficacy was assessed on the basis of HZ burden of illness (HZ‐BOI) scores over 30 days (BOI‐30AUC ). Secondary outcomes included HZ‐BOI scores through 30 to 90 days (BOI‐30‐90AUC ) and 90 to 180 days (BOI‐90‐180AUC ), quality of life (QoL) outcomes, concomitant analgesic consumption, and the incidence of PHN. Adverse events were recorded to evaluate safety. Results: The BOI‐30AUC values were 92.55 and 112.72 for the treatment and placebo groups, respectively ( P  < 0.01). Both the BOI‐30‐90AUC and BOI‐90‐180AUC in the treatment group were lower than those in the placebo group ( P  < 0.01). The incidence of PHN at 90 days was significantly less than that at 180 days in the treatment group ( P  = 0.036). A better improvement in QoL was found in the treatment group ( P  < 0.05). There was a greater decrease in analgesic use in the treatment group as compared to the placebo group ( P  < 0.05). No serious adverse events were observed. Conclusions: Ultrasound‐guided CRB represented an early intervention and preventive strategy to reduce the BOI due to acute HZ in the cervical dermatome region, and might be feasible to reduce the incidence of PHN.